American Society of Clinical Oncology (ASCO) Cervical Cancer Prevention Program: A Hands-On Training Course in Nepal. (2021) - Phoolcharoen, Natacha; Kremzier, Megan; Eaton, Vanessa; Sarchet, Vanessa; Acharya, Sandhya Chapagain; Shrestha, Eliza; Carns, Jennifer; Baker, Ellen; Varon, Melissa Lopez; Karmacharya, Saujanya; Aryal, Saujanya; Richards-Kortum, Rebecca; et al.
Abstract : Cervical cancer is the leading cause of death among women in Nepal. The American Society of Clinical Oncology (ASCO) and The University of Texas MD Anderson Cancer Center collaborated with international and local experts to hold a cervical cancer prevention course in Nepal in November 2019. The course included didactic lectures and a hands-on workshop. The didactic lectures included the epidemiology of cervical cancer globally and locally, cervical cancer screening guidelines, human papillomavirus vaccination, colposcopy and visual inspection with acetic acid (VIA), cervical dysplasia, and cervical cancer treatment. The hands-on workshop consisted of four stations: (1) VIA; (2) colposcopy, cervical biopsy, and endocervical curettage; (3) thermal ablation; and (4) loop electrosurgical excision procedure (LEEP). A train-the-trainer model short course was held by the international faculty to assist six local faculty to become familiar with the instruments, procedures, and models used in the hands-on training stations. Forty-two people (84% gynecologist, 8% radiation oncologist, and 8% other) attended the course. Following the course, the international faculty visited the regional hospitals for additional educational activities. Increased knowledge in cervical cancer screening guidelines and ability in performing VIA, colposcopy and cervical biopsy, thermal ablation, and LEEP were reported by 89%, 84%, 84%, 87%, and 84% of participants, respectively, from the postcourse on-site evaluations. From the 6-month follow-up survey, all respondents reported that they had made practice changes based on what they learned in the course and had implemented or tried to implement the cervical cancer screening guidelines presented at the course. In conclusion, the course evaluations suggested an improvement in participants' ability to perform cervical cancer screening and diagnostic procedures and reported the changes in practices after training.